Enhancement of Biocontrol Activities of Trichoderma Harzianum Rifai Through Protoplast Fusion - Wong, Mui Yun (1999)
Enhancement of the biocontrol activities of Trichoderma harzianum Rifai against two soilborne pathogens, Sclerotium rolfsii and Ganoderma boninense through protoplast fusion was attempted. Mycelial cultures from three indigenous isolates from the rhizospheres of groundnut (IMI 378843), chilli (IMI 378844) and oil palm (IMI 378841) were used for the protoplast isolation and fusion studies. The result showed that the optimum release of viable protoplasts was obtained when mycelial cultures at the exponential stage was incubated for 4 h in Novozym 234 (Sigma) as the lytic enzyme at concentration of 7 mg/ml dissolved in 0.7 M NaCI and 0.6 M sorbitol. Pretreatment of mycelium v.ith 0.01 M 2-mercaptoethanol gave no Significant difference on protoplast yield of the three isolates studied. The protoplast yield was within the range of 10⁶-10⁸ protoplasts/ml and the average size of the protoplasts was 2.5-10.0 µm. Chemically induced fusion, using polyethylene glycol (pEG), among the three isolates yielded a total of 12 fusants. germinated 18 h after incubation in liquid Protoplast Regeneration Medium (PRM). When plated on solid PRM, the fusants regenerated into single colonies between 24-48 h after incubation. Of the 12 fusants obtained, five fusants showed non-parental type in isozyme analysis. They were further evaluated based on the cultural and morphological analysis, biomass growth, antagonistic activities against S. Tolfsii and G. boninense, tolerance to commonly used fungicides, and the ability to produce two extracellular lytic enzymes, B-l,3-glucanase and chitinase.